O regionalności XVII-wiecznych kazań pogrzebowych. Część III: druki gdańskie - Pihan-Kijasowa, Alicja; Motyl, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
Funeral sermons published in the 17th century in Poland constitute an impressive collection of more than 600 texts. They must have been printed by all the contemporary printers in Małopolska, Wielkopolska, Silesia, Mazowsze, Pomerania and the Eastern Borderlands. They were written by monks and priests of various denominations, some of them seasoned preachers, and some clergy without experience or talent. Fairly large numbers of these sermons have been preserved as part of the heritage of each of the printing centres. However, barely 17 funeral addresses printed in the 17th century in Danzig have survived, representing less than 3% of the total domestic output of this type of literature. With this article in mind, we have selected seven sermons written by Catholic priests and representatives of other denominations. The final research material formed the basis for deliberations on 17th century Polish, with special emphasis placed on its regional characteristics. Before that, information was gleaned on the printing circles in Gdańsk, the origins and professional education of the contemporary printers and the sermons’ authors. While we do not know many of the authors’ biographies, there are some common linguistic features in the texts that can be traced back to the Pomerania region by means of historical dialectology; for example disruptions in the distribution of the vowels i and y, de-palatalization of the sound l (pronounced lyst), de-palatalization of the sounds ḱ, ǵ (pronounced ludzky, Pomorsky), a de-palatalized ending of the instrumental case in plural nouns, adjectives and pronouns (pronounced cnotamy, wielkimy), replacing consonantal clusters Š, Ś, S and several less significant linguistic facts. A majority of the above mentioned features occur in all the texts printed in Gdańsk. However, there are sermons in which the linguistic features characteristic of Pomerania (and of the authors, or editors) are particularly frequent (e.g. the sermon by Andrzej Skata, published by Filip Chrystian Rhete).